Expressing the isolation experienced by young women with anorexia nervosa - Gaviña, Jea Alyssa R.
Anorexia nervosa (AN) is a psychiatric illness that affects mostly adolescent girls and young women. It's characterized by the restriction of food intake that results into an extremely lowered body weight (DSM 5). Like most psychiatric illnesses, AN needs to be addressed seriously and those who suffer from it need professional help and rehabilitation. However, AN is rarely discussed in the Philippines and those who suffer from AN find it difficult to talk about their disorder and experiences, hence making them feel isolated. There are many factors that result into these feelings of isolation. Many studies have observed that poor coping strategies, responses to difficulties, decision-making and social skills are commonly experienced by individuals with AN. In the Philippines, there are scarce documentations and studies on AN, making it a poorly understood phenomena in the country. This scarcity in studies and records is caused by the very nature of AN, wherein an individual with the disorder is unwilling to seek help or are simply unaware of the disorder and its consequences. it should also be considered that there is low awareness about it the country. The problem addressed in this study is the isolation that those who suffer from AN in the Philippines experience because of these multiple factors. The researcher makes use of qualitative methods such as conducting surveys and interviews to have a better understanding of the problem at hand. As such, the aim is to find a way to oppose stigma, raise awareness, and educate people about AN, as well as make those who suffer from the disorder feel safe, valid, and supported, allowing them to speak up about their disorder and ask for treatment.